The Ambivalence of Far-Right Women: Hate, Trauma, Gender, and Neoliberalism in Contemporary Japan - Yoshida, Yutaka (Journal of interpersonal violence, 2024)
While far-right movements are commonly associated with masculinity and women are in the minority, it is notable that they often play significant roles within these movements. To deepen our understanding of the motivations behind women’s participation, this study challenges Blee’s argument that women’s motivations for participating are shaped by their interactions with other members. By using the psychosocial method devised by Hollway and Jefferson and developed by Gadd, the present study argues that women’s pre-participation experiences can play a vital part in drawing them to the movements. Through analyzing the life stories of six far-right women in Japan and conducting an in-depth case study of three of them, the study aims to uncover a wide range of experiences that may initially appear unrelated to far-right ideology but ultimately led these subjects to become involved in far-right movements. It highlights the importance of paying attention to their complex subjectivities, which are formed by the interplay between their unique trajectories and societal transitions concerning gender norms, particularly within the era of neoliberal “emancipation.” The study finds that the duality of far-right movements, which combine conservatism with deviance, enables some women to express paradoxical desires that they experience in response to living through a transitional era.